Pengaruh Sistem Pengupahan terhadap Kinerja Dosen Swasta di Propinsi Riau - Afrijal, Afrijal (Komunitas Manajemen Kompetitif, 2015)
Abstract: The purpose of this study was to determine the effect of influence of compensation on the performance of the lecturer of private college lecturer in Riau province. The whole object of research lecturer in Private University in three colleges namely Riau Islamic University (UIR), Lancang Kuning University (UNILAK) and the University of sand Pengaraian (UPP) at the Faculty of Economics and Management Studies Program Akuntasni totaling 68 people consisting of as many UIR 31 people, 25 and UPP UNILAK as many as 12 people with saturated sampling technique. The method used in this study is a quantitative method. The results showed that the compensation to the performance of 0,160 professors Keywords: compensation, performance of the lecturer